Piloting a mental health intervention for young adults in poverty enrolled in post-secondary education in post-conflict regions in Colombia: a study protocol - Zimmerman, Annie; García Durán, María Camila; Araya, Ricardo; Avendano, Mauricio; Hessel, Philipp; Díaz, Yadira; Peña Niño, Omar Dario; Donetto, Sara; Escobar Lux, Martha; Idrobo, Fabio (Frontiers in Psychiatry, 2023)
Background: Colombia has endured more than five decades of internal armed conflict, which led to substantial costs for human capital and mental health. There is currently little evidence about the impact of incorporating a mental health intervention within an existing public cash transfer programme to address poverty, and this project aims to develop and pilot a mental health support intervention embedded within the human capital programme to achieve better outcomes among beneficiaries, especially those displaced by conflict and the most socioeconomically vulnerable.The study will consist of three phases: semi-structured one-to-one interviews, codesign and adaptations of the proposed intervention with participants and pilot of the digital intervention based on cognitive behavioural therapy and transdiagnostic techniques. to determine its feasibility, acceptability, efficacy, and usefulness in 'real settings'. Results will inform if the intervention improves clinical, educational and employment prospects among those who use it.Results: Knowledge will be generated on whether the mental health intervention could potentially improve young people's mental health and human capital in conflict-affected areas?We will evaluate of the impact of potential mental health improvements on human capital outcomes, including educational and employment outcomes.Findings will help to make conclusions about the feasibility and acceptability of the intervention, and it will assess its effectiveness to improve the mental health and human capital outcomes of beneficiaries. This will enable the identification of strategies to address mental health problems among socioeconomically vulnerable young people that can be adapted to different contexts in in low and middle-income countries.